Behavioral Response of Giant Freshwater Prawn (Macrobrachium rosenbergii) to the Folding Traps - Fatmawati, Riska; Jhonnerie, Romie; Nofrizal; Widhiastika, Dhita; Hendrizal, Andri; Prianto, Eko; Oktorini, Yossi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
The behavior of the giant freshwater prawn (Macrobrachium rosenbergii) towards folding traps is significant to identify, given its complex movement patterns and dependence on the fishing gear. This study aimed to investigate the behavioral responses of M. rosenbergii to folding traps by examining spatial movement patterns and assessing trap effectiveness across three time periods (morning, noon, and night). To achieve this, an experiment using a behavioral event analysis approach was employed to reconstruct movement trajectories, X–Y coordinates, and behavioral phases. Furthermore, the Mann–Whitney U test was utilized to compare the distributions of entry and exit frequencies as an indicator of trap retention efficiency. The results showed that prawns exhibited adaptive, stepwise spatial behavior, beginning with external exploration characterized by zigzag paths, circular movements, and approach–retract cycles, before entering the trap with an average latency of 8–10 minutes. Furthermore, 95 of 160 individuals (59.38%) successfully entered the trap, whereas 65 (40.62%) exited after initial contact. The Mann–Whitney test confirmed a significant difference between entry and escape numbers (U=63;p